Exposing an “Intangible” Cognitive Skill among Collegiate Football Players: Enhanced Interference Control - Wylie, Scott A.; Bashore, Theodore R.; Van Wouwe, Nelleke C.; Mason, Emily J.; John, Kevin D.; Neimat, Joseph S.; Ally, Brandon A. (Frontiers in Psychology, 2018)
American football is played in a chaotic visual environment filled with relevant and distracting information. We investigated the hypothesis that collegiate football players show exceptional skill at shielding their response execution from the interfering effects of distraction (interference control). The performances of 280 football players from National Collegiate Athletic Association (NCAA) Division I football programs were compared to age-matched controls in a variant of the Eriksen flanker task (Eriksen & Eriksen, 1974). This task quantifies the magnitude of interference produced by visual distraction on split-second response execution. Overall, football athletes and age controls showed similar mean reaction times (RTs) and accuracy rates. However, football athletes were more proficient at shielding their response execution speed from the interfering effects of distraction (i.e., smaller flanker effect costs on RT). Offensive and defensive players showed smaller interference costs compared to controls, but defensive players showed the smallest costs. All defensive positions and one offensive position showed statistically smaller interference effects when compared directly to age controls. These data reveal a clear cognitive advantage among football athletes at executing motor responses in the face of distraction, the existence and magnitude of which vary by position. Individual differences in cognitive control may have important implications for both player selection and development to improve interference control capabilities during play.